State of play in the molecular presentation and recognition of anti-tumor lipid-based analogues - Praveena, T.; Le Nours, Jérôme (Frontiers in Immunology, 2024)
The Natural Killer T cells (NKT) are a unique subset of T lymphocytes that recognize lipid-based antigens that are presented by the monomorphic MHC-I-like molecule, CD1d. Over 30 years ago, the discovery of the glycolipid α-Galactosylceramide (α-GalCer) from the marine sponge Agelas mauritianus, as a potent activator of the invariant Natural Killer T (iNKT) cells, has attracted great attention for its use in cancer immunotherapy. However, α-GalCer can initiate both pro-inflammatory T helper cell 1 (Th1) and anti-inflammatory Th2 type immune responses that can result in either enhanced or suppressed immunity in a somewhat unpredictable manner. Th1 polarized immune response is often correlated with an optimal anti-tumor immunity, and therefore α-GalCer did not fully offer the desired potential as an anti-tumor therapeutic. Over the past decades, considerable efforts have then been invested into the design and development of novel synthetic α-GalCer analogues that will direct a more efficient immune response towards the production of Th1 biased cytokines. In this minireview, we will discuss how subtle modifications in the chemical nature of a number of α-GalCer derivatives varied immune responses. Whilst some of these analogues showed potential in enhancing stability within CD1d and directing favourable immune responses for tumor immunotherapy, their responses in mice also highlighted the need for further research in humanized models to overcome translational challenges and optimize therapeutic efficacy.